Development and validation of microsatellite markers for Barnyard Millet obtained by partial genome assembly: Microsatellite markers of barnyard millet - Tomar, Rukam Singh (Annals of Arid Zone, 2023)
Barnyard millet (Echinochloa esculenta L.)  is grown for human consumption as well as fodder. Barnyard millet is the second most important small millet after finger millet. An Ion S5 Next Generation Sequencer (NGS) was used to sequence the 400bp DNA library of barnyard millet to obtain a draft genome and for mining of microsatellite markers. The De novo assembly yielded assembled reads of 59,67,79,933 bp with 11,39,481 contigs. A total of 46,157 SSRs were identified from 11,39,481 contigs examined. The number of sequences containing SSR were 41,591 and the number of sequences containing more than 1 SSRs were 3,867.  Fifteen SSR markers were validated among the 30 accessions of barnyard millet. The average percentage polymorphism of markers was 66.54 % with average polymorphism information content (PIC) of 0.28 and average SSR primer index (SPI) of 0.57.  These microsatellite markers can be used for fine linkage mapping and genes/QTLs tagging for genetic improvement of target traits in barnyard millet and related crops.